PERAN PENYULUH AGAMA HINDU DALAM PEMBENTUKAN KARAKTER ANTI RADIKALISME - kunti ayu vedanti (Dharma Duta, 2017)
Radicalism is a violent that act commited in an attempt to instill a certain understanding or against the government. Radicalism has adverse effect on humans till nature. Radicalism also violates human rights, as well as ini acts that use dangerous weapons, radicalism causes natural destruction. Based on fact that radicalism is extremely dangerous, the prevention of radicalism is the responsibility of all parties. In the Hindu religion community, there is a known by existence of religious counselor of Hindu. The Hindu counselor is someone who proclaimed the Vedic scriptures to the Hindus. Relevant to the goal of Hindu religion, which is to achieve a happy life for all creatures, the Hindu religious instructors are required to convey the teaching of Hindu religion that is useful to solve various problems of human life. Similiarly, in the prevention of radicalism. The participation of Hindu counselors are expected to form the character of anti-radicalism by practicing the practical teaching of Hinduism as a guide of life. Moreover, the participation of Hindu counselors are as well as a carrier of knowledge and national insight to enhance the love of the country.